OPTIMIZATION OF INDEPENDENT WORK OF STUDENTS IN THE LIGHT OF INNOVATIVE EDUCATIONAL TECHNOLOGIES WHEN STUDYING INTERNAL MEDICINE. - Kudria I. P.; Shevchenko T. I.; Shaposhnyk O. A.; Tretiak N. G. (Eastern Ukrainian Medical Journal, 2020)
The article deals with the organization of independent work of students with the active use of innovative educational technologies that open up new opportunities for optimizing the educational process in a medical university and set teachers tasks that are aimed at developing modern forms and methods of its implementation, which contribute to the organization of professional activities at a qualitatively new level. The purpose of the article is to analyze various aspects and methods of independent work of students in the light of innovative educational technologies in the study of internal medicine in order to optimize the educational process. The site of the Ukrainian Medical Stomatological Academy has a web-page of Internal Medicine Department № 1, where students can find guidelines for independent work for IV and VI courses in preparation for classes in Ukrainian, Russian and English using the Internet. Future doctors use multimedia technologies at meetings of the student scientific society, during educational events and open lessons for school students, organizing educational hours among the student audience, which expands opportunities for creativity, develops competence and mobility, and strengthens the role of independent work. Using the information of the group "department of internal medicine № 1" in the social network Facebook, students not only master modern learning technologies in the era of the so-called information society, but also master communication skills with other people, learn to search in different ways and analyze certain information. As a result of the functioning of the computer class, students have the opportunity to pass the test control of the initial and final levels of knowledge in the current and final practical classes, test tasks from the license exam "KROK-2", which encourages them to more thorough preparation for classes in internal medicine. In the course of studying internal medicine, it is important to create and optimize conditions for independent work of students for further development of professional competencies of a doctor: the ability to work with information on the global Internet, to use the capabilities of modern computer systems and innovative technologies to solve professional problems. The use of innovative educational technologies in the organization of independent work of future doctors at Internal Medicine Department № 1 contributes to a deeper study of internal medicine, the formation of professional knowledge and their application in practice, strengthening the connection between educational and scientific work, and also optimizes the learning process of medical students, which ensures the dynamic development of a specialist’s personality, activates his creative and clinical thinking, helps to implement an individual approach to training and meets the requirements of modern medical education.